A Gelation‐Stabilized Strategy toward Photothermal Architecture Design for Highly Efficient Solar Water Evaporation. Issue 5 (24th March 2021) - Zhang, Wei; Chang, Qing; Xue, Chaorui; Yang, Jinlong; Hu, Shengliang
Abstract : Constructing a solar‐driven interfacial evaporation system with effective energy confinement and conversion abilities is highly desired for seawater desalination and wastewater purification without the need of a complex and costly infrastructure. Herein, a powerful universal approach for the bottom‐up design of the photothermal conversion system using 0D nanoparticles is reported. That is, the integration of nanoparticles with cotton fibers (CFs) is first formed by surface adsorption and then reinforced by in situ cross‐linked polyvinyl alcohol chains. The developed photothermal architecture exhibits a superior water evaporation performance, excellent durability, and high adaptability in various environments. By this approach, the resulting system of carbon dots assembled on the surface of CFs is able to evaporate water with a rate of 2.32 kg m −2 h −1 and a solar‐to‐vapor efficiency of 93.6% under 1 sun irradiation, remarkably superior to the evaporators made by other black photothermal sheets. Thereby, the presented method enables potentially low‐cost, abundant, and tunable 0D nanomaterials for rationally designing ideal solar conversion structures. Abstract : A novel and universal method is provided for constructing the solar‐driven interfacial evaporation system with effective energy confinement and conversion abilities through 0D nanoparticles.